Classification of fracture and non-fracture groups by analysis of coherent X-ray scatter - Dicken, A. J.; Evans, J. Paul O.; Rogers, Keith; Stone, N.; Greenwood, Charlene; Godber, S. X.; Clement, J. G.; Lyburn, Iain Douglas; Martin, R. M.; Zioupos, Peter (Springer, 2016)
Osteoporotic fractures present a significant social and economic burden, which is set to rise commensurately with the aging population. Greater understanding of the physicochemical differences between osteoporotic and normal conditions will facilitate the development of diagnostic technologies with increased performance and treatments with increased efficacy. Using coherent X-ray scattering we have evaluated a population of 108 ex vivo human bone samples comprised of non-fracture and fracture groups. Principal component fed linear discriminant analysis was used to develop a classification model to discern each condition resulting in a sensitivity and specificity of 93% and 91%, respectively. Evaluating the coherent X-ray scatter differences from each condition supports the hypothesis that a causal physicochemical change has occurred in the fracture group. This work is a critical step along the path towards developing an in vivo diagnostic tool for fracture risk prediction.